Urgensi Rekonstruksi Pengaturan Praktek Perjanjian Perdagangan Melalui E-Commerce - Dwi Mayasari, I Dewa Ayu; Gde Rudy, Dewa (Jurnal Komunikasi Hukum, 2021)
In general, the agreement is made face-to-face. However, along with technological developments, agreements can now be made through electronic media (internet) or E-commerce. Through E-commerce, it has brought changes in human activities because through the internet, any transaction can be done, including making an agreement. However, many problems arise in transactions conducted electronically, such as trading transactions or buying and selling online. The problems that can be conveyed are firstly the urgency to reconstruct the practice of trade agreement arrangements through E-Commerce, second form of legal protection against parties who are disadvantaged in practicing trade agreements through E-Commerce and thirdly the settlement that can be carried out if there is a dispute in the practice of a trade agreement through E -Commerce. This research uses normative legal research, with a statutory approach and analysis of legal concepts and uses primary, secondary and tertiary legal sources. Furthermore, it is collected systematically using documentation studies and added with supporting data. The conclusion of this research is that the reconstruction of trade agreement practice arrangements is very urgent to be carried out for philosophical, sociological, juridical and practical reasons, both forms of legal protection against the aggrieved party, namely the Civil Code, ITE Law, Consumer Protection Law and the third settlement that can be done if a dispute occurs is through the Litigation, Non Litigation or BPSK channels.